The impact of COVID-19 on morbidity and mortality in neck of femur fracture patients: a prospective case-control cohort study. (1st November 2020) - Ward, Alex E.; Tadross, Daniel; Wells, Fiona; Majkowski, Lawrence; Naveed, Umna; Jeyapalan, Rathan; Partridge, David G.; Madan, Suvira; Blundell, Chris M.
Abstract : Aims: Within the UK, around 70, 000 patients suffer neck of femur (NOF) fractures annually. Patients presenting with this injury are often frail, leading to increased morbidity and a 30-day mortality rate of 6.1%. COVID-19 infection has a broad spectrum of clinical presentations with the elderly, and those with pre-existing comorbidities are at a higher risk of severe respiratory compromise and death. Further increased risk has been observed in the postoperative period. The aim of this study was to assess the impact of COVID-19 infection on the complication and mortality rates of NOF fracture patients. Methods: All NOF fracture patients presenting between March 2020 and May 2020 were included. Patients were divided into two subgroup: those with or without clinical and/or laboratory diagnosis of COVID-19. Data were collected on patient demographics, pattern of injury, complications, length of stay, and mortality. Results: Overall, 132 patients were included. Of these, 34.8% (n = 46) were diagnosed with COVID-19. Bacterial pneumonia was observed at a significantly higher rate in those patients with COVID-19 (56.5% vs 15.1%; p =< 0.000). Non respiratory complications such as acute kidney injury (30.4% vs 9.3%; p =0.002) and urinary tract infection (10.9% vs 3.5%; p =0.126) were also more common in those patients with COVID-19. Length of stay was increased by a median of 21.5 days in patients diagnosed with COVID-19 (p < 0.000). 30-day mortality was significantly higher in patients with COVID-19 (37.0%) when compared to those without (10.5%; p <0.000). Conclusion: This study has shown that patients with a neck of femur fracture have a high rate of mortality and complications such as bacterial pneumonia and acute kidney injury when diagnosed with COVID-19 within the perioperative period. We have demonstrated the high risk of in hospital transmission of COVID-19 and the association between the infection and an increased length of stay for the patients affected. Cite this article: Bone Joint Open 2020;1-11:669–675.